2021
DOI: 10.1109/jstars.2021.3079699
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Model for Detecting Heavy Precipitation Using GNSS-Derived Zenith Total Delay Measurements

Abstract: In recent years, precipitable water vapor (PWV) have been widely used in heavy precipitation prediction, which is obtained from a conversion of the zenith total delay (ZTD) of the GNSS signal. Since the parameter directly estimated for the tropospheric delay from GNSS data processing is the ZTD, this study investigated the feasibility of directly using ZTD to predict heavy precipitation. Based on the finding that, prior to a heavy precipitation events, ZTD was likely to start with a duration of continuous rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…(1) This practice can avoid a possible degradation in the accuracy caused by errors introduced from the use of meteorological variables in the conversion process from ZTD to PWV. ( 2) Various studies have also confirmed that the time series of ZTD and PWV have quite similar variation trends [35,36], indicating that the two variables may have analogical influences on the linear calibration exercises. The second novelty lies in the fact that the statistical parameter of mean Julian Date (MJD), reflecting the time-varying characteristics of other atmospheric variables, was first introduced to an application of this type.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…(1) This practice can avoid a possible degradation in the accuracy caused by errors introduced from the use of meteorological variables in the conversion process from ZTD to PWV. ( 2) Various studies have also confirmed that the time series of ZTD and PWV have quite similar variation trends [35,36], indicating that the two variables may have analogical influences on the linear calibration exercises. The second novelty lies in the fact that the statistical parameter of mean Julian Date (MJD), reflecting the time-varying characteristics of other atmospheric variables, was first introduced to an application of this type.…”
Section: Introductionmentioning
confidence: 88%
“…The retrieval of ZTD time series over the 14-year study period at the selected ten stations was conducted by using Bernese GNSS Software Version 5.2 [46]. The detailed data processing strategies were generally the same as those adopted in our previous studies [35], including the double-difference approach, the elevation angle cutoff of 3 • , the Vienna Mapping Function 1, and the operational International GNSS Service Finals clocks and orbits [47,48]. Regarding temporal issues, a 27-hour observation window was selected, and the temporal resolution of ZTD estimates as well as estimation spacing were both set to 5 min [49,50].…”
Section: Retrieval Of Gnss-ztdmentioning
confidence: 99%
See 2 more Smart Citations
“…2) GNSS PWV: It is noteworthy that while ZTD has been shown to exhibit a close relationship with atmospheric humidity [17], [53], which can also circumvent the introduction of error sources associated with converting ZTD to PWV, it cannot be directly considered as a representative measure of water vapor content in the atmosphere. Additionally, numerous previous studies have unequivocally demonstrated the benefits of assimilating PWV into NWP models [33], [54], [55].…”
Section: B Retrieval Of Near-real Time Gnss Tropospheric Products 1) ...mentioning
confidence: 99%